An appraisal of the laws for the treatment and rehabilitation of drug dependants in Malaysia / Zafani Zainudin, Rozianti Mohamed Hanaphi and Tariq Azfar Maketab - Zainudin, Zafani; Mohamed Hanaphi, Rozianti; Maketab, Tariq Azfar (2007)
As a partial fulfillment of our course, we have conducted research on the treatment and rehabilitation of drug dependants in Malaysia. We looked at the implementation and enforcement of the Drug Dependants (Treatment and Rehabilitation) Act 1983. In our research, we focused on the enforcement of treatment and rehabilitation provided in the Act. Enforcement as referred in the Act referred to acts involving many parties such as the judiciary, Anti-Dadah Task force and private persons. In addition, we looked at the history of drugs in Malaysia and also looked at the terminology used concerning drug dependants. Though there are many terms available, the one used in the statutes is "drug dependants". Drug dependants are similar to drug abusers and drug addicts. Thus, the term is used interchangeably in this research. We have conducted a survey on the awareness of the people about the drug scenario in Malaysia as well as the laws governing drugs. Apart from that, we also conducted an interview with the rehabilitation officer in Dengkil Rehabilitation Centre. With the hard work and cooperation of many parties, we manage to gather a lot of information and opinions relating to the treatment and rehabilitation of drugs dependants. Our research shows that the existing laws are sufficient but commitment from many parties is needed to make them work effectively.